Study on Heterotrophic-Autotrophic Denitrification Permeable Reactive Barriers (HAD PRBs) for In Situ Groundwater Remediation - Liu, Fei.; Huang, Guoxin; Fallowfield, Howard; Guan, Huade; Zhu, Lingling; Hu, Hongyan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
"Study on Heterotrophic-Autotrophic Denitrification Permeable Reactive Barriers (HAD PRBs) for In Situ Groundwater Remediation(3y (Bis an unmatched reference work on PRBs for groundwater in situ remediation. It proposes a novel HAD PRB approach for nitrate-contaminated groundwater remediation, and provides a systematic and clear explanation of design concepts and denitrification mechanisms. The book consists of four chapters, each of which covers key aspects of HAD PRBs. It provides rich, easy-to-follow illustrations, tables and references. Unique as a comprehensive reference work on the subject, it will serve as a valuable resource for all engineers and scientists active in environmental science and engineering, groundwater science, engineering and molecular biology. Prof. Fei Liu works at China University of Geosciences (Beijing), China. Dr. Guoxin Huang works at Beijing Academy of Food Sciences, China. Both Prof. Howard Fallowfield and Prof. Huade Guan work at Flinders University, Australia. Assistant Engineer Lingling Zhu works at Geological Publishing House, China. Assistant Engineer Hongyan Hu works at Hydrogeology and Engineering Geology Prospecting Institute of Heilongjiang Province, China.s
General introduction -- Heterotrophic-autotrophic denitrification (HAD) for groundwater remediation in an aerobic environment -- Heterotrophic-autotrophic denitrification permeable reactive barriers (HAD PRBs) for groundwater remediation -- Identification of bacterial diversity in the inoculums.
Keywords: Environmental sciences; Hydraulic engineering; Biotechnology; Environmental pollution; Environment; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Environmental Engineering/Biotechnology.; Environmental Science and Engineering; Hydrogeology